Comparison of Consumer Acceptances of Frozen Pizzas Assessed at Central Location Test (CLT) vs Home Use Test (HUT) - Puntarika Ratanatriwong; May Suk Yeung; Citra Jusup; Matrid Ndife (Agriculture and Natural Resources, 2006)
Selection of sensory testing location plays an important role on the sensory evaluation. Not only does test location define how product is sampled and perceived, but different results may be obtained from different test sites with a given sample sets and consumers as well. This study was to investigate the consumer perceptions on frozen pizzas as affected by various testing locations: central location test (CLT) vs. home use test (HUT), and to determine if the tested products matched the consumer ideal product profile. In CLT, 137 panelists assessed frozen spicy chicken and pepperoni using the acceptance test based on various attribute categories: appearances, tastes, textures and overall acceptance. However, data analysis (∝=0.05) using chi-square and Student’s t-test was based on 46% of panelists who returned HUT results. Both spicy chicken and pepperoni pizzas showed no significant difference of consumer acceptances assessed in CLT and HUT based on all attributes except crispness and tenderness. Although the overall taste of spicy chicken showed the potential (p=0.06) that test locations may show an influence on consumer acceptance if more data was collected. Both frozen pizzas were not significant different from the consumer ideal product profiles. CLT was recommended for the consumer acceptance test of frozen pizzas due to its advantages in validity of responses, target consumer, convenient and economical aspects despite a caution that some texture attributes were influenced by the test location.